Spanish Physical Education Teachers’ Perceptions about Their Preparation for Inclusive Education - Jorge Rojo-Ramos; Fernando Manzano-Redondo; José Carmelo Adsuar; Ángel Acevedo-Duque; Santiago Gomez-Paniagua; Sabina Barrios-Fernandez (Children, 2022)
The prevailing rights and quality of life approaches call for the inclusion of people with diversity and/or disabilities in society, including their participation in the educational system. Therefore, different institutions are urging countries to take action to ensure that students with disabilities receive the accommodations and supports they need within the framework of inclusive education. The idiosyncrasies of physical education (PE) classes can be an opportunity to encourage the participation and inclusion of these students. Thus, this study aims to evaluate the PE teachers’ perception about their preparation to address inclusive education. The study involved 260 Spanish primary and secondary PE teachers who answered a sociodemographic questionnaire, three dichotomic questions about their initial and ongoing preparation and the Evaluation of Teacher Training for Inclusion Questionnaire (CEFI-R). PE teachers believe that they have not received the necessary initial preparation and they consider it important to assist in ongoing courses to address their students’ diverse needs. PE teachers are aware of the importance of inclusive education and perceive greater difficulties in secondary education. PE teachers also showed a good predisposition to teach students with special educational support needs, especially found in primary school teachers through the CEFI-R Dimension 1, with statistically significant differences.